Sex differences in pacing strategies during open water swimming. - Hara, R.; Fujimoto, T.; Miki, J.; Ueno, K. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Open water swimming (OWS) is a swimming event in which swimmers swim in the ocean or a river, etc. The 10 km OWS is the most recent Olympic swimming event, which began in 2008, and in recent years the races have become faster. One reason for this is that the top long-distance swimmers are competing in the OWS as dual swimmers as well as competitive swimmers. For example, at the 2022 World Swimming Championships, the winner of the 10 km OWS also won the 1500 m freestyle swimming race. World Aquatics has announced that the equirements to qualify for the Paris Olympics are to finish third or higher at the 2023 World Championships and 10th or higher at the 2024 World Championships. Therefore, in order to qualify for the Olympics, not only the swimmers' swimming ability but also their race strategy will be very important. The competition time for the 10km OWS is approximately 2 hours, which is an endurance exercise similar in exercise duration to that of an athletics marathon race; in developing a race strategy for the 10km OWS, coaches and swimmers will make a comprehensive assessment of environmental factors such as weather, water temperature, and currents. On the other hand, OWS races are postponed during thunderstorms, so in big OWS events such as the World Championships and the Olympic Games, men's and women's races are held on different days to avoid cancellation of all races as much as possible. Nikolaidis et al. (2018) reported gender differences in race strategy for channel crossing swims, which are longer than regular OWS events, however, much remains unknown about gender differences in race strategy for the 10 km OWS. It would be of great help to swimmers and coaches if race strategies for the next day's race could be developed based on race strategies in either the men's or women's race. Luis et al. (2017) compared pacing strategies by level for the 10 km OWS at the 2015 World Championships. The results showed that medalists and finalists exhibited similar pacing to slower swimmers at the beginning and middle of the race, but they swam faster in the last spurt of the final lap. Santiago et al. (2019) showed that elite open water swimmers at the 2017 World Championships successfully used a race strategy was presented. They suggest that the swimmers who placed in the top 10 in the race swam within 10-20 seconds of the lead swimmer. Because of this variety of developments in race strategies for faster 10 km OWS, it is necessary to examine the differences between men and women in the major 10 km OWS race strategies in recent years. Therefore, the aim of the present study was to examine the sex differences in pacing during top 10 elite swimmers of the recent six major 10km OWS races.